Z dziejów parafii Wniebowzięcia NMP w Kraśniku po kasacie klasztoru kanoników regularnych - Prejs, Roland (Archiwa, Biblioteki i Muzea Kościelne, 2018)
The history of the parish dedicated to the Assumption of the Blessed Virgin Mary in Kraśnik after the dissolution of the monastery of the Canons Regular is an interesting and worth studying case of the conversion of the former monastic parish to the diocesan one, which, however, retained at least the vestiges of the presence of monks, both in sacred buildings and in certain manifestations of pastoral practice. The latter requires more careful study and description. There were two similar cases in the diocese of Lublin – two Piarist parishes in Chełm and Opole Lubelskie before 1864; other monasteries, though active in the pastoral field, were not involved in running a parish. A more thorough study on the history of this parish could probably shed some light on how the Church performed pastoral work when faced with the restrictions imposed by the Tsar after the January Uprising. The years after 1970, especially the construction of the church in Kraśnik Fabryczny, are part of the most recent period of history and should be the subject of a separate study.